New flavone from the leaves of local medicinal plant Corydyline terminalis Kunth - Amzad Hossaina M.; Raj Nagoorub M.; Jualang A. Gansau (2012)
A new flavone was isolated from the ethyl acetate extract of the leaves of medicinal plant Corydyline terminalis kunth collected from Sabah Malaysia. It was characterized as 3’-hydroxy-5,6,7,4’-tetramethoxyflavone with the help of 1H-NMR, 13C-NMR, COSY, DEPT 45, DEPT 90, DEPT 135 and mass spectral data. It is a new plant and also isolated compounds first time reported from this plant